2023
DOI: 10.1111/den.14489
|View full text |Cite
|
Sign up to set email alerts
|

Updates in narrow‐band imaging for colorectal polyps: Narrow‐band imaging generations, detection, diagnosis, and artificial intelligence

Abstract: Narrow‐band imaging (NBI) is an optical digital enhancement method that allows the observation of vascular and surface structures of colorectal lesions. Its usefulness in the detection and diagnosis of colorectal polyps has been demonstrated in several clinical trials and the diagnostic algorithms have been simplified after the establishment of endoscopic classifications such as the Japan NBI Expert Team classification. However, there were issues including lack of brightness in the earlier models, poor visibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 117 publications
(185 reference statements)
0
6
0
Order By: Relevance
“…In contrast, our model can achieve good results with simple white-light colonoscopy alone. This outcome limits the convenience and widespread applicability of their models [ 9 ]. One of the contributions of our study is that our AI model works better for white light than NBI images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our model can achieve good results with simple white-light colonoscopy alone. This outcome limits the convenience and widespread applicability of their models [ 9 ]. One of the contributions of our study is that our AI model works better for white light than NBI images.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Azam et al [ 8 ] built an AI model with both wight-light and NBI images to improve the accuracy of their model. However, the NBI or other enhanced method has their weaknesses [ 9 ]. The efficiency of NBI is highly dependent on bowel preparation, and the image of NBI is darker than the white-light images.…”
Section: Introductionmentioning
confidence: 99%
“…First generation NBI was launched in 2006 as a part of two endoscopic systems, EVIS LUCERA SPECTRUM (in Japan and UK) and EXERA II (elsewhere) ( 31 ). Images generated by first-generation NBI were not ideal due to low brightness, and studies indicated that the adenoma detection rate (ADR) was comparable between NBI and WLE ( 32 , 33 ).…”
Section: Electronic Enhancing Techniques (Virtual Chromoendoscopy)mentioning
confidence: 99%
“…These models used a stronger xenon lamp and a new signal processor which worked by elimination of filter mechanism as well as reduction of image noise, thereby producing brighter sharp images. It also allowed an optical magnification of ×45 power with a simple press of a button ( 27 , 31 ). A recent meta-analysis of 11 RCTs involving 4,491 patients found that ADR for second-generation NBI was better compared to HD-WLE (OR: 1.28; 95% CI: 1.05–1.56; P=0.02) ( 34 ).…”
Section: Electronic Enhancing Techniques (Virtual Chromoendoscopy)mentioning
confidence: 99%
“…NBI is an optical digital imaging technique wherein two selected wavelengths (415 + −30 nm and 540 + −30 nm) enhance the structural aspects of the surface of the mucosa and existing blood vessels [ 12 ]. Numerous studies have shown that NBI is capable of accurate tissue characterization [ 8 , 13 , 14 , 15 ]. This strong evidence led to the development of the NBI International Colorectal Endoscopic (NICE) classification, which allows for an accurate differentiation between adenomatous and hyperplastic polyps in vivo by analyzing the color, surface pattern, and vascular pattern of DCPs with NBI [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%